Influence of Environmental Knowledge and Fashion Consciousness on Green Purchase Intention of Sustainable Fashion Products - Zahra - Syauqina; Putut - Haribowo; Yusmar Ardhi Hidayat (Admisi dan Bisnis, 2022)
The growing awareness of claims about the negative impacts on the environment causes to lead fast fashion brands to shift their production from fast to sustainable collections. In line with the previous transformation, customers intend to purchase sustainable fashion products by considering their fashion consciousness and environmental knowledge. This study has two goals: (1) analyzing the influence of environmental knowledge on green purchase intention of sustainable fashion products. (2) analyzing the influence of fashion consciousness on green purchase intention of sustainable fashion products. Purposive sampling was used to select 100 respondents who bought fashion brands H&M and ZARA. This study used multiple regression analysis. This study proved that environmental knowledge and fashion consciousness positively influences green purchase intention of sustainable fashion products. The higher the environmental knowledge, the higher the extent of green purchase intention of sustainable fashion. Sustainable fashion industries should maintain product designs, attractive attributes, and variations of styles of sustainable apparel collections. They should emphasize the benefit of purchasing sustainable fashion products to save the environment through intense campaigns.